Nursery care of patients after restorative proctocolectomy in the course of ulcerates colitis - Kozłowska, Elżbieta; Cierzniakowska, Katarzyna; Popow, Aleksandra; Szewczyk, Maria T.; Banaszkiewicz, Zbigniew (Pielęgniarstwo Chirurgiczne i Angiologiczne/Surgical and Vascular Nursing, 2018)
Thanks to the possibility of maintaining natural bowel movement, restorative proctocolectomy has become the chosen method in surgical treatment of ulcerative colitis. However, an intestinal pouch created in this way may cause numerous metabolic and activity problems for patients. Shortening the passage of the digestive tract and changes in ileum microflora make taking antidiarrhoeal agents and keeping a strict diet necessary. A very important element of taking care of patients after restorative proctocolectomy is education in terms of regulating bowel movements, prophylaxis, and the necessity to treat complications, especially inflammation states of the intestinal pouch.